Pergamon, Türkei. Pergamon. Die Arbeiten des Jahres 2019 - Pirson, Felix (e-Forschungsberichte des DAI, 2020)
In 2019, the Pergamon Excavation concentrated on works within the new research programme »The Transformation of the Pergamon Micro-region between Hellenism and the Roman Empire« (TransPergMikro). The completion of the excavations of the so-called Banqueting House on the eastern slope of the city-hill has yielded important new results on the construction, equipment and use of this unusual site. The first systematic excavations in the amphitheatre of Pergamon revealed a niched wall as limitation of the arena, the floor of the arena and a construction to accumulate water in its interior. Archaeological building research continued in the amphitheatre as well as in the extra-urban thermal bath. The archaeological and geophysical follow-up investigations on the tumuli Yığma Tepe and X-Tepe were completed. A new project in the surroundings of the Asklepieion has provided initial insights into land use and development structure. The work in the area surrounding Pergamon through archaeology and physical geography concentrated on exemplary sections of the landscape as well as on individual outstanding sites and their natural context on the south-western edge of the valley of the Kaikos (Bakırçay).